Model Based Parameter Estimation: Theory and Applications - Bock, Hans Georg; Carraro, Thomas; Jäger, Willi; Körkel, Stefan; Rannacher, Rolf; Schlöder, Johannes P. (Springer, 2013)
Parameter Estimation and Optimum Experimental Design for Differential Equation Models: H.G. Bock, St. Körkel, J.P. Schlöder -- Adaptive Finite Element Methods for Parameter Identification Problems: B. Vexler -- Gauss-Newton Methods for Robust Parameter Estimation: T. Binder, E. Kostina -- An Optimal Scanning Sensor Activation Policy for Parameter Estimation of Distributed Systems: D. Ucínski -- Interaction between Experiment, Modeling and Simulation of Spatial Aspects in the JAK2/STAT5 Signaling Pathway: E. Friedmann, A. C. Pfeifer, R. Neumann, U. Klingmüller , R. Rannacher -- The Importance and Challenges of Bayesian Parameter Learning in Systems Biology: J. Mazur, L. Kaderali -- Experiment Setups and Parameter Estimation in Fluorescence Recovery After Photobleaching Experiments: A Review of Current Practice: J. Beaudouin, M. S. Mommer, H. G. Bock, R. Eils -- Drug Resistance in Infectious Diseases: Modeling, Parameter Estimation and Numerical Simulation: Le Thi Thanh An, W. Jäger -- Mathematical Models of Hematopoietic Reconstitution after Stem Cell Transplantation: A. Marciniak-Czochra, Th. Stiehl -- Combustion Chemistry and Parameter Estimation: M. Fischer, U. Riedel -- Numerical Simulation of Catalytic Reactors by Molecular-Based Models: O. Deutschmann, St. Tischer -- Model-Based Design of Experiments for Estimating Heat-Transport Parameters in Tubular Reactors: A.Badinski, D. Corbett -- Parameter Estimation for a Reconstructed SOFC Mixed-Conducting LSCF-Cathode: Th. Carraro, J. Joos -- An Application of Robust Parameter Estimation in Environmental Physics: G. Herzog, F. R. Vogel -- Parameter Estimation in Image Processing and Computer Vision: Ch. S. Garbe, B. Ommer.
Description based upon print version of record
Keywords: Konferenzschrift -- 2009 -- Heidelberg; Differentialgleichung; Mathematisches Modell; Optimale Versuchsplanung; Parameterschätzung